Echography in anesthesiology, intensive care and emergency medicine: A beginner's guide - Greco, Frédéric (Springer Paris : Imprint: Springer, 2010)
Are you looking for the essentials you need to learn the basics of echography for anesthesiology, intensive care and emergency medicine? This is what this book offers you! These few pages condense the essential knowledge to make getting started with echography in emergency situations easier. Ultrasounds are presented in great detail in order to facilitate and optimize the medical diagnosis process. As a doctor, you will first be placed in front of the machine in order to take the pictures that will serve to answer the questions asked. Just as the author did, you will realize that, when facing the patient with the machine, the best echographic examination is worth nothing without a good clinical examination. As a "beginner's guide", this book also offers self-training procedure that lays the foundations of the "FAST" learning method. This FAST Program of Echography allows you to learn the process by watching, feeling and talking. This training course is based on an ancient methodology that centers on the learning of a manual gesture: 'practice makes perfect'. This book will show you that you can quickly master this Program of Echography, and will in turn increase your self-confidence when taking care of your patients. Have a nice trip through the fascinating world of ultrasounds!